Quality of Driver’s Licence Services at the Minahasa Police Administrative Organisation Unit - Steven Tarore; Juwita Yulianti Silaban; Meity Najoan; Delma Marlina Pasla; Siti Fathimah (Technium Social Sciences Journal, 2024)
This research aims to describe the quality of service for the issuance of new SIM C and the factors that influence the Minahasa Police Administration Unit. The research method used is qualitative descriptive method and data collection using observation, interview, and documentation techniques, the data obtained are analyzed with interactive analysis models. Informants as data sources are officers and applicant for a new SIM C at the Minahasa Police Administration Unit. The result of this study show that the quality of service for the issuance of a new SIM C at the Minahasa Police Administration Unit in terms of indicators of physical tangible, reliability, responsiviness, assurance, and empathy can be said to be not good. The factors that affect the quality of SIM services are system factors in the form of networks and the absence of a queuing system, personal factors in the form of officer behavior and performance, and human resources factors. Researchers provide recommendations to the Minahasa Police Administration Unit to improve the facilities and infrastructure needed for effective and efficient services, provide anti-scalper socialization to the community, conduct training and guidance for officers to be better and competent, add officers to optimize services, create a queuing system, conduct monitoring and evaluation.